2009
DOI: 10.1007/s10661-008-0716-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dry season surface, ground, and treated water quality in the Cape Coast municipality of Ghana

Abstract: This aim of this monitoring was to assess water quality in a dry season for the Cape Coast municipality in Ghana, which has been experiencing chronic water shortages. Fifteen different sampling stations--four surface, five ground, and six tap water samples--were analyzed for physicochemical and microbiological parameters during January to April 2005. Levels or trends in water quality that may be deleterious to sensitive water uses, including drinking, irrigation, and livestock watering have been noted with ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…This study, along with other water quality assessments in Africa, indicates that moderate to heavy fecal contamination is the greatest health risk associated with drinking water (Bordalo and Savva-Bordalo 2007;Quagraine and Adokoh 2010;Howard et al 2003;Omezuruike et al 2008;Ayanlaja et al 2005;Zamxaka et al 2004;Clasen and Bastable 2003;Shayo et al 2007) while physiochemical contamination is a less important consideration. Greater attention should be given to implementing methods to reduce fecal contamination.…”
Section: Discussionmentioning
confidence: 54%
“…This study, along with other water quality assessments in Africa, indicates that moderate to heavy fecal contamination is the greatest health risk associated with drinking water (Bordalo and Savva-Bordalo 2007;Quagraine and Adokoh 2010;Howard et al 2003;Omezuruike et al 2008;Ayanlaja et al 2005;Zamxaka et al 2004;Clasen and Bastable 2003;Shayo et al 2007) while physiochemical contamination is a less important consideration. Greater attention should be given to implementing methods to reduce fecal contamination.…”
Section: Discussionmentioning
confidence: 54%
“…A monitoring programme executed in Cambodia [3] reported elevated levels of lead, selenium, molybdenum and chromium only in a limited number of cases. Mercury was marginally detected in some surface and ground waters in Ghana [4]. Another study conducted in Ghana [5] also found concentrations of lead, uranium and boron above the World Health Organisation (WHO) Guide Values (GVs) in restricted areas.…”
Section: Introductionmentioning
confidence: 97%
“…Also iron and manganese can be present in surface and ground waters at levels ranging from 0.5 to 50 mg/L and from 1 渭g/L to 10 mg/L, respectively [8]. Concentrations exceeding WHO GVs, respectively 0.3 mg Fe/L and 0.4 mg Mn/L, were found in Cambodia [3], Zimbabwe [9], Ghana [4,5], Cameroon [10], Pakistan [11] and Bangladesh [6]. Sharaky et al [12] observed in the groundwater in the Nile delta area concentrations of trace elements lower than the standard limits, except for iron, manganese and nickel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have documented coliform pollution of shallow wells and groundwater (Obiri-Danso et al 2009), rivers (Abdul-Razak et al 2009), rural and municipal domestic water supply (Ampofo 1997;Quagraine and Adokoh 2009), "sachet" and hand-tied drinking water (Dodoo et al 2006;Obiri-Danso et al 2003) in different parts of Ghana. As important as these studies are in revealing the health dangers associated with coliform bacteria, none of the papers confronted the issue through a well designed sampling programme to assess the sources of these pollutants in treated waters based on prevailing environmental conditions.…”
Section: Introductionmentioning
confidence: 99%